Inter‐ and intrasex habitat partitioning in the highly dimorphic southern elephant seal. Issue 4 (29th January 2021) - Hindell, Mark A.; McMahon, Clive R.; Jonsen, Ian; Harcourt, Robert; Arce, Fernando; Guinet, Christophe
Abstract: Partitioning resources is a key mechanism for avoiding intraspecific competition and maximizing individual energy gain. However, in sexually dimorphic species it is difficult to discern if partitioning is due to competition or the different resource needs of morphologically distinct individuals. In the highly dimorphic southern elephant seal, there are intersexual differences in habitat use; at Iles Kerguelen, males predominantly use shelf waters, while females use deeper oceanic waters. There are equally marked intrasexual differences, with some males using the nearby Kerguelen Plateau, and others using the much more distant Antarctic continental shelf ( 2, 000 km away). We used this combination of inter and intrasexual behavior to test two hypotheses regarding habitat partitioning in highly dimorphic species. (a) that intersexual differences in habitat use will not appear until the seals diverge in body size and (b) that some habitats have higher rates of energy return than others. In particular, that the Antarctic shelf would provide higher energy returns than the Kerguelen Shelf, to offset the greater cost of travel. We quantified the habitat use of 187 southern elephant seals (102 adult females and 85 subadult males). The seals in the two groups were the same size ( 2.4 m) removing the confounding effect of body size. We found that the intersexual differences in habitat use existed before the divergence in body size. Also, we found that the amount of energy gained was the same in all of the major habitats. This suggests that the use of shelf habitats by males is innate, and a trade‐off between the need to access the large benthic prey available on shelf waters, against the higher risk of predation there. Intrasexual differences in habitat use are another trade‐off; although there are fewer predators on the Antarctic shelf, it is subject to considerable interannual fluctuations in sea‐ice extent. In contrast, the Kerguelen Plateau presents more consistent foraging opportunities, but contains higher levels of predation. Habitat partitioning in this highly dimorphic species is therefore the result of complex interplay of life history strategies, environmental conditions and predation pressure. Abstract : Partitioning resources is key to avoiding intraspecific competition and maximizing individual energy gain. However, in sexually dimorphic species partitioning can be due to either competition or the different resource needs of morphologically distinct individuals. Our study demonstrates that habitat partitioning in highly dimorphic species is the result of complex interplay of life history strategies, environmental conditions, and predation pressure.